Imagery in Hebrew Proverbs: A Selected Collection - Waheed Safeyeh (دراسات فی اللغه العربیه و آدابها)
Proverbs are considered a literary and artistic work. This is the reason major books were written about the process of collecting and explaining the origin of proverbs. Proverbs have eloquent designs and narrate highly applicable human experience. They sometimes teach manners and rules of behavior. It seems the originators of proverbs were wise men who knew about the secrets of life and appreciated the general understanding of people and could extract the gist of that understanding and reflect on it. Although poetry is a better outlet for imagination, proverbs can as a type of literary language which yield itself to analysis of the same images we can find in poems. In this study, we examine a number of Hebrew proverbs based on a comparative tradition which includes irony, simile, and metaphor. It is hoped that this study will usher in larger and more applied investigations. The result of this study indicate that the proverbs attributed to Solomon (PBUH) are closer to philosophy while the proverbs attributed to the Jews are more application-oriented and reflect their lifestyle. Moreover, Hebrew proverbs, particularly those which intends to counsel, characteristically include more accessible imagery.